Catalytic Hydrogenolysis of CFC-12 (CCl2F2) over Bimetallic Palladium Catalysts Supported on Activated Carbon - Song, J.H.; Seo, K.W.; Mok, Y.I.; Park, K.Y.; Ahn, B.S. (Korean Institute of Chemical Engineers, 2002)
Experiments were conducted for the hydrogenolysis of CFC-12 (CCl 2F2) to CH2F2 over bimetallic palladium catalysts (Pd-Bi, Pd-Ru) supported on activated carbon. The characteristics of the bimetallic palladium catalysts were examined with ICP, XRD, TPD, TEM, and N2 physisorption/H2 chemisorption and the Pd-F formation was identified by XPS analysis. The catalytic activity of the bimetallic palladium catalyst (Pd-Bi/C, or Pd-Ru/C) was superior to that of the monometallic palladium catalyst. The bimetallic palladium catalysts showed much higher conversion rates (more than 99% of it was converted) than did the monometallic palladium catalyst (<92%) and were deactivated to a lesser extent, even at high temperatures (>320 °C). The bimetallic components maintained the good dispersion of the Pd on the activated carbon support.
Keywords: Activated carbon; Bimetals; Catalyst activity; Catalysts; Chemisorption; Inductively coupled plasma; Palladium; Temperature programmed desorption; Transmission electron microscopy; X ray diffraction analysis; Catalytic hydrogenolysis; Chlorofluorocarbons